Niedom. Przekraczanie idei domu rodzinnego w mieszkaniu migracyjnym - Jewdokimow, Marcin; Łukasiuk, Magdalena (Załącznik Kulturoznawczy, 2023)
The photo-essay aims at presenting selected characteristics of migrants’ dwelling (an untypical dwelling formation) such as: temporality, dialectics of openness on others and closeness in private space or poor material culture. Authors’ interpretations these characteristics allow for redefining migrants’ dwelling as a non-home, a concept introduce as a result of their boarder studies on dwelling cultures in the context of migration. A non-home is neither a simple nor a sophisticated anti-thesis of a home. It rather consists of a mixture of components, directly transferred from home and beyond. Interpretations of a non-home illustrate selected dimensions of contemporary transformations of culture.Presented photos were captured during our field study between 2007 and 2010 in Warsaw